Spot IT internal intranet website / Rekha Nair C.Gamgadharan Nair - Rekha Nair , C.Gamgadharan Nair (2002)
When we look at the sheer volume of information stored by corporations today, including reams of printed information like computer documentation, procedures, specifications, and reference documents, we quickly see the argument for taking information online. Users no longer have time to wade through a shelf full of manuals to find some obscure tidbit of information, and companies can no longer justify the cost of printing all this information without any guarantee that users are actually reading it. Then there is the problem of keeping all that printed information up-to-date. Many companies are already using intranets to deliver information to internal users. The term intranet refers to the fact that the Web (or other Internet applications) are being run completely on the inside of a private network, often without a direct connection to the Internet. There are a number of information resources and transactions that are potential candidates for an intranet. Considering the rapid growth of intranets, a study was conducted on the impact of intranets in Malaysian organizations. Since feedback is slow, this study was limited to sending out questionnaires only. The analysis was not done as the author was given the freedom to concentrate on the development of the system proposed (this will be discussed later). The author has taken the opportunity to introduce intranet and the recent issues involving intranets in this first part of the thesis First of all, the author starts off with a discussion on the questions that were posed in the questionnaire that were sent to Malaysian organizations to get response on the impact intranet has on them. Following which, the author continues to tackle subjects like definition of intranets, history of intranets, i sues to consider when building an intranet, key intranet questions to be asked before deciding to build an intranet, intranet myths, intranet reference model and finally to the core of the research in hand, what materials on the internet have say about intranet benefits and challenges. These materials were very valuable in the process of designing the questionnaire. At the same time, studies on the impact of intranets on foreign organizations and also the use of intranet in the state of Sabah were also conducted and the outcomes of these findings are also explained in the literature review section of this thesis. In addition to the research topic in hand, an internal web site within an intranet for a mock organization, West Indies Oil Refiners, called SPOT I.T is also proposed to be developed, the third and fourth chapter of this thesis will discuss in detail on the proposed development of this web site. SPOT I. T is in tune to the intranet concept; it is intended to serve I. T services to all employees of the organization. Even though it is I. T department based, all employees from any department can equally benefit from the content it has to offer. LT services has been chosen as the theme of this website due to the fact, apart from human resource, information technology has always been the concern of all in the organization, this is even more true with the implementation of intranets. SPOT I.T will provide forms such as complaint and request forms for users to fill in I. T based complaints and services, apart from this, they can also check what their status of complaint/request is. They will also be able to find I. T agreements, project details, information on personnel policies and benefits, lists of I. T related links and tools, information on I. T training and seminars, frequently asked questions, I. T department chart, interesting places to visit and also a calendar which lets users know what interesting events are happening every day. SPOT I.T is developed using the evolutionary prototype model. A few existing intranet websites were studied to get ideas on functional, non-functional requirements and design concepts. The author had to research through materials to find suitable development software for SPOT 1.T. The findings of these materials are presented in chapter three, system analysis and requirement. In the fourth chapter, system design, the author discusses the design of the system. SPOT I.T architecture is divided into administrator module and user module. The functional design of the system will be presented using data flow diagrams and structure charts. Following this the design of databases will be discussed through presentations of entity relationship diagram and samples of table designs. The main source of research for the design of SPOT I. T was the research findings in literature review. Certain examples of existing intranet related sites were used as foundations to determine the requirements and design of the system. In the fifth chapter, the author will discuss briefly on how the system requirements were transformed to implementation. This discussion will be mainly on the coding and the database connection. The hardware and software required for the implementation will also be stated. The sixth chapter will include the stages of testing that was conducted to ensure the system is not only error free but also meet the requirement. Finally, the seventh chapter will conclude with the evaluation of the system. The system strengths and weaknesses will be studied, at the same time future enhancements that can be made to the system will also be analyzed. The author will also share knowledge, which was gained, and the difficulties faced throughout the project. The most important aim of this whole project is the intention to prove that intranet based applications definitely can make a difference in an organization.